QUALITATIVE AND QUANTITATIVE ANALYSIS OF MEDICINAL CHEMICALS OF “ JAMU REMATIK DAN PEGAL LINU “ IN MAGELANG REGION - Haresmita, Perdana Priya; Wardani, Arief Kusuma; Pradani, Missya Putri Kurnia; Permatasari, Lina (Universitas Muhammadiyah Kalimantan Timur, 2023)
Jamu for rheumatism and